PRMT3 at the crossroads of inflammation: dual roles in metabolic reprogramming and immune dysregulation in chronic diseases - Hou, Huining; Meng, Jiaojiao; Chen, Yingqing; Zhang, Xili; Yang, Zhuqing; Wang, Qianqian; Zheng, Min; Jiang, Zebo (Frontiers in Immunology, 2026)
Protein arginine methyltransferase 3, a type I PRMT family member, plays pleiotropic roles in chronic inflammatory diseases through its catalysis of asymmetric dimethylarginine modifications. Chronic inflammation, marked by metabolic dysregulation, immune dysfunction, and tissue fibrosis, drives diverse pathologies including non-alcoholic fatty liver disease, chronic kidney disease, and atherosclerosis. In this review, we comprehensively dissect the multifaceted contributions and molecular mechanisms of PRMT3 in inflammation-associated disorders. Mechanistically, PRMT3 aggravates inflammatory-metabolic dyshomeostasis in chronic inflammation via LXRα/HIF-1α methylation, thereby accelerating vascular calcification and fibrosis. Paradoxically, it simultaneously suppresses antiviral immunity and facilitates tumor immune evasion, underscoring its dual role as a molecular “double-edged sword”. Notably, PRMT3 inhibitors such as SGC707 demonstrate preclinical promise in modulating lipid metabolism and curtailing tumor progression. However, challenges persist regarding tissue specificity and off-target toxicity, necessitating further refinement. Collectively, these results provide a new molecular basis for therapeutic approaches targeting PRMT3.